Changing Economic Strategies in the Ecsed Marsh: An Example of Renewal in Nagyecsed - Zoltán-Borzován, Eszter (Ethnographica et Folkloristica Carpathica, 2023)
The Ecsed Swamp was formed in the New Holocene Era in the lowest areas of Nyírség and Szatmár Plains. Besides the protective nature of the swamp, it was a significant source of livelihood for the local population – loach fish collecting (csikász), bird hunting and egg collecting (pákász) were the main occupations of the “swamp people”. The Ecsed Swamp, which once covered almost 432 km2 was drained at the end of the 19th century that caused significant changes in everyday life and farming. The inhabitants of the so-called “Loach land” (Csíkország) tried to dig up and cultivate marshy areas even before the drainage. Burning, cutting and cleaning were already known among the swamp people, since this was the only way to carry out farming activities in this area. In their frustration the swamp people effected by the drainage tried to obtain land for cultivation. They worked on the lands purchased by the Károlyi noble family. More prosperous ones also built farms on the border of the neighbouring villages, thus the process of homesteading began. In the 21st century, the cultivation of agricultural land in the area of former swamps is causing significant problems since water shortage is now characteristic towhole Europe. Reedfires in the former swamp areais a phenomenon that exists to this day. With the transformation of landscape and ways of farming and living, the need to apply different economic strategies arose, which I will discuss t in my research study with case studies from the 19th and 21st centuries.